2017
DOI: 10.1590/1518-8345.1721.2918
|View full text |Cite
|
Sign up to set email alerts
|

Scale of attitudes toward alcohol - Spanish version: evidences of validity and reliability

Abstract: Objective:validate the Scale of attitudes toward alcohol, alcoholism and individuals with alcohol use disorders in its Spanish version. Method:methodological study, involving 300 Colombian nurses. Adopting the classical theory, confirmatory factor analysis was applied without prior examination, based on the strong historical evidence of the factorial structure of the original scale to determine the construct validity of this Spanish version. To assess the reliability, Cronbach’s Alpha and Mc Donalid’s Omega co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
4
8
0
4
Order By: Relevance
“…Therefore, professionals who had previously worked with drug-dependent patients exhibited decreased fear and anxiety. If we compare these findings with the degree of professionals’ satisfaction indicated by our findings, we can observe professionals’ negative attitudes towards alcoholics and, therefore, less motivation for providing care [24]. This coincides with the result of perceptions about alcoholics and studies that did not distinguish the substance consumed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, professionals who had previously worked with drug-dependent patients exhibited decreased fear and anxiety. If we compare these findings with the degree of professionals’ satisfaction indicated by our findings, we can observe professionals’ negative attitudes towards alcoholics and, therefore, less motivation for providing care [24]. This coincides with the result of perceptions about alcoholics and studies that did not distinguish the substance consumed.…”
Section: Discussionsupporting
confidence: 79%
“…The Seaman–Mannello scale is a discrete quantitative scale, which is categorized, created, and validated by its authors in Buffalo (Nueva York) and later translated into Portuguese in Brazil by Pillon. A back-translation of the Portuguese version into Spanish was carried out by Villar to apply it in Bolivia, and it was later validated in its Spanish version for its use in Colombia by León and Vargas [ 24 ]. It consists of 30 items grouped into five subscales, to which the participants had to respond, according to their level of agreement or disagreement using a five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different instruments used for measuring nursing professionals' attitudes when working with alcoholics. However, most studies have used Seaman-Mannello scale (Allen, 1993;De Vargas & Labate, 2003, 2005Navarrete & Villar, 2004;Vasquez & Pillon, 2005;De Vargas & Luis, 2008;León & Vargas, 2017) and, as we previously mentioned, the results obtained by those studies were very similar to ours. All those studies concluded Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 19 July 2018 doi:10.20944/preprints201807.0364.v1…”
Section: Discussionsupporting
confidence: 88%
“…The Seaman-Mannello scale is a discrete quantitative scale, categorized, created, and validated by its authors in Buffalo (Nueva York) and later translated into Portuguese in Brazil by Pillon. A back-translation of the Portuguese version into Spanish was carried out by Villar to apply it in Bolivia, and was later validated in its Spanish version for use in Colombia by León and Vargas (León & Vargas, 2017). It consists of 30 items grouped into five subscales to which the participants had to respond according to their level of agreement or disagreement using a five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%